Pandemics through the lens of occupations. (16th February 2022) - Chopra, Anand; Devereux, Michael B.; Lahiri, Amartya
Abstract: We outline a macro‐pandemic model where individuals can select into working from home or in the market. Market work increases the risk of infection. Occupations differ in the ease of substitution between market and home work and in the risk of infection. We examine the evolution of a pandemic in the model as well as its macroeconomic and distributional consequences. The model is calibrated to British Columbian data to examine the implications of shutting down different industries by linking industries to occupations. We find that endogenous choice to self‐isolate is key: it reduces the peak weekly infection rate by two percentage points but reduces the trough consumption level by four percentage points, even without policy‐mandated lockdowns. The model also produces widening consumption inequality, a fact that has characterized COVID‐19. Résumé: Les pandémies envisagées à travers le prisme des professions . Nous décrivons un modèle de macro‐pandémie où les individus peuvent choisir de travailler à domicile ou sur le marché. Le travail sur le marché augmente le risque d'infection. Les professions diffèrent par la facilité de substitution entre le marché du travail et le travail à domicile, et par le risque d'infection. Nous examinons l'évolution d'une pandémie dans le modèle ainsi que ses conséquences macroéconomiques et distributionnelles. Le modèle est calibré sur les données de la Colombie‐Britannique pour examiner les implications de la fermeture de différentes industries en reliant les industries aux professions. Nous constatons que le choix endogène de s'auto‐isoler est essentiel : il réduit le taux d'infection hebdomadaire maximal de deux points de pourcentage, mais réduit le niveau de consommation minimal de quatre points de pourcentage, même sans les verrouillages imposés par la politique. Le modèle produit également une inégalité de consommation croissante, un fait qui a caractérisé le COVID‐19.